Late-Onset Sacsinopathy Diagnosed by Exome Sequencing and Comparative Genomic Hybridization. (December 2013) - Pyle, Angela; Griffin, Helen; Duff, Jennifer; Bennett, Shona; Zwolinski, Simon; Smertenko, Tania; Yu-Wai Man, Patrick; Santibanez-Koref, Mauro; Horvath, Rita; Chinnery, Patrick F.
Abstract Abstract: The molecular diagnosis of adult-onset autosomal recessive cerebellar ataxias remains challenging because of genetic heterogeneity. However, recently developed molecular genetic techniques will potentially revolutionize the diagnostic approach. Here we set out to define the genetic basis of the ataxia in two brothers with no molecular diagnosis. Clinical evaluation was followed by whole-exome second-generation sequencing and comparative genomic hybridization to determine the diagnosis. Whole-exome sequencing identified a hemizygous novel spastic ataxia of Charlevoix-Saguenay (SACS) stop-codon mutation in both brothers (c.13048G→T, p.E4350*) that was present in the mother, but not the father. Comparative genomic hybridization revealed a 0.7-Mb deletion on chromosome 13q12.12 in both brothers, which included SACS and was heterozygous in the asymptomatic father. The milder phenotype, caused by a whole-gene deletion and a stop-codon mutation in SACS, indicates a loss-of-function mechanism in late-onset autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS), and illustrates the importance of chromosomal rearrangements in the investigation of adult-onset ataxia.